2005
DOI: 10.1152/ajpregu.00446.2004
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of free and receptor-bound leptin in normal twins

Abstract: Free and receptor-bound leptin may be regulated by different mechanisms. Genes that influence the concentration of these fractions may have an important functional bearing. We determined circulating leptin receptor concentrations, bound as well as free leptin concentrations, and body composition in 24 monozygotic (MZ) and in 22 dizygotic (DZ) twin pairs. Bound leptin and leptin receptor concentrations were inversely correlated with body fat content. Free leptin concentrations were directly correlated with body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Although tracking per se appears not to have been demonstrated previously, Jordan et al [27] showed that circulating SLR concentrations, and leptin concentrations, bound or free, exhibited adjusted heritability estimates of 0.28 for free leptin, 0.73 for bound leptin, and 0.55 for SLR, in 24 monozygotic and 22 dizygotic twin pairs, suggesting an intrinsic genetic influence, which could be compatible with tracking. In comObes Facts 2011;4:461- 468 Tracking of Leptin and Its Soluble Receptor 467 in regain.…”
Section: Discussionmentioning
confidence: 88%
“…Although tracking per se appears not to have been demonstrated previously, Jordan et al [27] showed that circulating SLR concentrations, and leptin concentrations, bound or free, exhibited adjusted heritability estimates of 0.28 for free leptin, 0.73 for bound leptin, and 0.55 for SLR, in 24 monozygotic and 22 dizygotic twin pairs, suggesting an intrinsic genetic influence, which could be compatible with tracking. In comObes Facts 2011;4:461- 468 Tracking of Leptin and Its Soluble Receptor 467 in regain.…”
Section: Discussionmentioning
confidence: 88%
“…Heritability for leptin and BMI traits has been reported previously, with evidence of shared genetic determination. 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the different prognostic effects of body fat accumulation markers imply differences in etiology, including genetic predisposition. This is supported by analysis of obesity phenotypes in twin studies, which show a genetic correlation of less than one that indicates only partly overlap between the genes determining these phenotypes [28,29]. In some of our previous studies, we did include analyses of waist and/or waist-to-hip ratios in relation to some gene variants, but the quantitative feature throughout the population range was not used in the analyses.…”
Section: Selection and Genotyping Of Variantsmentioning
confidence: 95%